Cranial osteopathy for children with cerebral palsy: a randomised controlled trial. Issue 6 (24th February 2011) - Wyatt, Katrina; Edwards, Vanessa; Franck, Linda; Britten, Nicky; Creanor, Siobhan; Maddick, Andrew; Logan, Stuart
Abstract : Objectives: To estimate the effect of cranial osteopathy on the general health and wellbeing, including physical functioning, of children with cerebral palsy. Design: Pragmatic randomised controlled trial. Participants: 142 children from Greater London and the South West of England, aged 5–12 years with cerebral palsy. Intervention: Participants were randomised to six sessions of cranial osteopathy with a registered osteopath or a waiting list with partial attention control (parents invited to participate in two semistructured interviews). Primary outcome measures: Blind assessment of motor function by physiotherapists using the Gross Motor Function Measure-66 (GMFM-66) and quality of life using the Child Health Questionnaire (CHQ) PF50 at 6 months. Secondary outcome measures: Parents' assessment of global health and sleep at 6 months, pain and sleep diaries at 10 weeks and 6 months, CHQ PF50 at 10 weeks and quality of life of main carer (Short Form 36) at 10 weeks and 6 months. Results: Compared with children in the control group, children in the osteopathy group demonstrated no statistically significant differences in GMFM-66 (mean difference 4.9, 95% CI −4.4 to 14.1), CHQ Physical Summary Score (mean difference 2.2, 95% CI −3.5 to 8.0) or CHQ Psychological Summary Score (mean difference 3.4, 95% CI −0.8 to 7.7). There were no significant differences between groups with respect to pain; sleep (either 'time asleep' or 'time to sleep'); or main carer's quality of life. Compared with children in the control group, carers of children receiving cranial osteopathy were nearly twice as likely to report that their child's global health had 'improved' at 6 months rather than 'decreased' or 'remained the same' (38% vs 18%; odds ratio 2.8, 95% CI 1.1 to 6.9). Conclusions: This trial found no statistically significant evidence that cranial osteopathy leads to sustained improvement in motor function, pain, sleep or quality of life in children aged 5–12 years with cerebral palsy nor in quality of life of their carers. Trial Registration ISRCTN45840554 http://www.controlled-trials.com